TEACHER CAREER MANAGEMENT AS A SYSTEM ACTIVITY OF THE MANAGER OF EDUCATIONAL ORGANIZATION - Дипломатова, Зоя Юрьевна (Bulletin of the Chuvash State Pedagogical University named after I Y Yakovlev, 2021)
В статье рассматривается процесс управления карьерным ростом учителя как системная деятельность руководителя образовательного учреждения. На основе метода функционального анализа автором статьи рассматриваются основные функции управления в контексте данного исследования: целеполагание, планирование, организация, регулирование, контроль. Показана взаимосвязь и взаимообусловленность этих функций как единой сложной системы. Описаны факторы, влияющие на результаты карьерного роста учителя: стаж учителя; требования федеральных государственных образовательных стандартов, профессионального стандарта «Педагог»; мотивы профессиональной деятельности учителя; личностные качества и возможности учителя; перспективы развития системы образования. На основе актуальных источников в статье рассмотрены современные тренды образования, обусловливающие профессиональное развитие педагога. В частности, на основе материалов национального проекта «Образование», включающего в себя федеральные проекты «Современная школа», «Успех каждого ребенка», «Цифровая образовательная среда», «Учитель будущего», «Социальная активность», автором статьи рассматриваются основные тренды развития Российского образования как факторы, обусловливающие профессиональное развитие и карьерный рост учителя. В статье отмечается важная роль национальной системы учительского роста и новой модели аттестации педагогических кадров в управлении карьерным ростом учителя. На основе проведенного анализа делается вывод о том, что управление карьерным ростом учителя является деятельностью, требующей системного подхода со стороны администрации. The article examines the process of managing the teacher’s career growth as a systematic activity of the head of an educational institution. Based on the method of functional analysis, the author of the article examines the main functions of management in the context of this study: goal-setting, planning, organization, regulation, control. The article shows the interconnection and interdependence of these functions as a single complex system. The article describes the factors influencing the results of the teacher’s career growth: teacher’s experience; requirements of the federal state educational standards, professional standard “Teacher”; motives of the teacher’s professional activity; personal qualities and capabilities of the teacher; prospects for the development of the education system. On the basis of current sources, the article examines modern trends in education that determine the professional development of a teacher. Basing on the materials of the National Project “Education”, which includes the federal projects “Modern School”, “Success of Every Child”, “Digital Educational Environment”, “Teacher of the Future”, “Social Activity”, the author of the article considers the main trends in the development of the Russian education as factors that determine the professional development and career growth of a teacher. The article stresses the important role of the national system of the teacher’s growth and the new model of attestation of teaching staff in the management of the teacher’s career growth. On the basis of the conducted theoretical research, it is concluded that the management of the teacher’s career development is an activity that requires a systematic approach of the administration.